Power, Masculinities, Southern Theory: An Interview with Raewyn Connell About Political Sociology - Connell, Raewyn; Seeliger, Martin; Villa Braslavsky, Paula-Irene (Journal of Political Sociology, 2023)
Raewyn Connell began work in political sociology in the 1960s and has not entirely stopped since. However, her approach to power now transcends a narrow focus on the state and extends to fields such as culture, education and gender. She is best known in Australia for her research on inequalities in schooling and on class structure, and internationally as a leading figure in studies of men and masculinities. More recently, under the title of Southern Theory, her work on the global dynamics of social science has contributed to debates about epistemology and the decolonization of knowledge. In her reflections on the prospects and challenges of political sociology, she emphasizes the workforce, the transformation of universities and the employment conditions of young scholars responsible for creating the future of the field.The Interviewers are Martin Seeliger and Paula-Irene Villa Braslavsky.